PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KUALITAS LABA PADA PERUSAHAAN FOOD AND BEVERAGES YANG LISTING DI BURSA EFEK INDONESIA PERIODE 2013-2015. - Irawati HM; Putri Sudirman (Jurnal Bisnis dan Kewirausahaan, 2017)
This study aims to examine and analyze and know how to influence the audit committee, managerial ownership, institutional ownership, and quality audits of the quality of earnings in the Food and Beverages Company listing on the Indonesia Stock Exchange Period 2013-2015. The data used in this research is quantitative data, ie data obtained from the company's financial statements. The data used in this research is secondary data yangdiperoleh of Indonesia Stock Exchange website via the internet (www.idx.co.id). The results of this study stated that the audit committee and audit quality positive and significant impact on the quality of earnings, managerial ownership has a negative correlation and no significant effect on the quality of earnings and similarly with institutional ownership negatively affects the quality of earnings. The results of this study showed that 40,1% of earnings quality is affected by the audit committee, managerial ownership, institutional ownership and audit quality, meaning that 59,9% of earnings quality is influenced by other variables outside variables used in this study.